External morphology of the immatures of polybia paulista (Hymenoptera: Vespidae) - Solis, Daniel Russ; Dias, Nathalia Baptista [UNESP]; Fox, Eduardo Gonçalves Paterson (De Gruyter, 2012)
The immatures of Polybia paulista Ihering were described using light and scanning electron microscopy and the results are compared with previous descriptions within the same or related wasps. This study is based on 2 whole nests collected in the municipality of Rio Claro, Sao Paulo, in Brazil. We have detected the existence of 5 larval instars. The main morphological alterations over development occur in the relative size of structures, yet certain structures appear with subsequent instars and become more evident later in development: increasing density in the number of body spines and papillae; the appearance of body setae in fifth-instar larvae; opening of spiracles upon second-instar larvae; 2 body shapes in fifth-instar larvae; the appearance of a lateral tooth on the mandibles of fourth instar; presence of spines on the maxillae of fifth-instar larvae; altered shape of galea and palps upon third-instar larvae from a cluster of sensilla to a conical elevation; and the appearance of spines on postmentum upon fourth-instar larvae. This way, the present study presents a detailed description of the immatures of P. paulista, and we hope the presented information can be useful to morphological, taxonomic, and phylogenetic studies.
Keywords: Development; Epiponini; Larvae; Myrapetra; Polistinae